Life estimation by varying the critical plane orientation in the modified Carpinteri-Spagnoli criterion (Fracture and Structural Integrity, 2015)
The modified Carpinteri-Spagnoli (C-S) criterion is a multiaxial high-cycle fatigue criterion based onthe critical plane approach. According to such a criterion, the orientation of the critical plane is linked to boththe averaged directions of the principal stress axes and the fatigue properties of the material. The latterdependence is taken into account through a rotational angle, ?. Then, the multiaxial fatigue strength estimationis performed by computing an equivalent stress amplitude on the critical plane. In the present paper, somemodifications of the original ? expression are implemented in the modified C-S criterion. More precisely, suchmodified expressions of ? depend on the ratio between the fatigue limit under fully reversed shear stress andthat under fully reversed normal stress (in accordance with the original expression), and can be employed formetals ranging from mild to very hard fatigue behaviour. Some experimental data available in the literature arecompared with the theoretical results in order to verify if the modified ?expressions are able to improve thefatigue strength estimation capability of the modified C-S criterion.
Keywords: Constant amplitude loading